Utilization of Spontaneous Alkyne-Gold Self-Assembly Chemistry as an Alternative Method for Fabricating Electrochemical Aptamer-Based Sensors - Olivan, Lars Alexander (Langmuir : the ACS journal of surfaces and colloids, 2024)
Electrochemical aptamer-based (E-AB) sensors are a promising class of biosensors which use structure-switching redox-labeled oligonucleotides (aptamers) codeposited with passivating alkanethiol monolayers on electrode surfaces to specifically bind and detect target analytes. Signaling in E-AB sensors is an outcome of aptamer conformational changes upon target binding, with the sequence of the aptamer imparting specificity toward the analyte of interest. The change in conformation translates to a change in electron transfer between the redox label attached to the aptamer and the underlying electrode and is related to analyte concentration, allowing specific electrochemical detection of nonelectroactive analytes. E-AB sensor measurements are reagentless with time resolutions of seconds or less and may be miniaturized into the submicron range. Traditionally these sensors are fabricated using thiol-on-gold chemistry. Here we present an alternate immobilization chemistry, gold-alkyne binding, which results in an increase in sensor lifetimes under ideal conditions by up to ∼100%. We find that gold-alkyne binding is spontaneous and supports efficient E-AB sensor signaling with analytical performance characteristics similar to those of thiol generated monolayers. The surface modification differs from gold-thiol binding only in the time and aptamer concentration required to achieve similar aptamer surface coverages. In addition, alkynated aptamers differ from their thiolated analogues only by their chemical handle for surface attachment, so any existing aptamers can be easily adapted to utilize this attachment strategy